Parapammene komaiana sp. n. a new Tortricidae from Russian Far East (Bollettino di zoologia agraria e bachicoltura, 2024)
A new species of tortricid moth, Parapammene komaiana sp. n., from Barabash-Levada (Russian Far East) is described. Externally the new species resembles some Parapammene moths like P. dichroramphana (Kennel, 1900) and P. glaucana (Kennel, 1901). The genitalia of P. komaiana are very similar to those of Parapammene reversa Kamai, 1999, but the cornuti of the new species are lined andnot clustered as in P. reversa; P. komiana aedeagus is rather narrow than in P. reversa.
Keywords: Lepidoptera Tortricidae; Parapammene komaiana; new species; Russian Far East